Progress in the field of animal models of antiphospholipid syndrome - Xinnan Gao; Dan Ma; Liangyu Mi; Jingwen Zhao; Qi An; Zhiying Guo; Baoqi Yang; Liyun Zhang; Ke Xu (Taylor & Francis Group, 2024)
Antiphospholipid syndrome (APS) is an autoimmune disease characterized by recurrent arteriovenous thrombosis and pathological pregnancy, accompanied by persistent antiphospholipid antibodies, (aPL). The incidence of APS is increasing year by year, clinicians lack of understanding of this type of disease, easy to misdiagnose and miss the diagnosis. Therefore, it is extremely important to establish a suitable animal model to reduce the process of disease development as much as possible and improve clinicians' understanding and understanding. This review will summarize the animal models of APS from the aspects of modeling methods, modeling mechanism, evaluation indicators and advantages and disadvantages of methods, providing a reference for finding an animal model highly similar to human APS, helping researchers to further clarify the pathogenesis of APS and find potential therapeutic targets, so as to achieve early diagnosis, early intervention, and ultimately improve the prognosis of patients.